Metafora Romantisisme pada Syair Risalatu Min Tahtil Ma’ Karya Nizar Qabbani (Kajian Balaghah) - Rusna, Dyo; Rohanda, Rohanda; Azzahra, Rachma Aini; Alandira, Palendika (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
This study aims to analyze the metaphor of romanticism in the poem "Risalatu Min Tahtil Ma'" by Nizar Qabbani. The approach used is the majaz theory which is a branch of the science of bayan, so that the romanticism in the poem can be revealed. This research method uses a descriptive qualitative method to describe phenomena in poetry. The results of the study show that there are 15 majaz that describe the feeling of heartbreak due to love in return. The poem deviates slightly from the traditional matrix structure which emphasizes the free-form style of the verse and binds the reader to the emotional resonance of metaphor. Imagery and language are one of the elements to convey complex feelings in this poem, the use of classical language seeks to make this poem easier to understand and maintain its poetic elegance. From the results of this study, it can be concluded that this poem describes deep longing and sadness, as well as conveying the importance of accepting human emotions and strengthening relationships with the homeland and personal identity.